Analisis Perubahan Garis Pantai di Pesisir Pantai Kabupaten Lamongan Menggunakan Data Citra Satelit Landsat 8 - Mochammad Fahreeza Yuniar Effendi; Hendrata Wibisana; Bagas Aryaseta (Universitas Batanghari Jambi, 2026)
Coastal shoreline change is a complex natural phenomenon that can cause significant impacts on coastal areas, such as land loss, infrastructure damage, and disruption of the community’s socio-economic activities. These impacts can be minimized if shoreline change monitoring is carried out periodically in vulnerable areas. Lamongan Regency, with its relatively long coastline, is an area highly susceptible to shoreline changes caused by abrasion and accretion. Therefore, research related to the dynamics occurring in this region is necessary. This study aims to identify shoreline change phenomena along the coast of Lamongan Regency during the 2016–2025 period. The method used in mapping shoreline changes involved processing Landsat 8 satellite imagery using NDWI in ArcGIS, followed by distance calculations using the Euclidean distance method and the Haversine formula, as well as conducting a statistical T-test on the results of both methods. The statistical two-sample T-test with equal variance indicated that there is no variance difference between the results obtained using the Euclidean distance method and the Haversine formula. Based on the calculation results, it was found that the greatest shoreline change due to abrasion during 2016–2025 occurred at Transect 1, specifically in Lohgung Village, Brondong District, with a change of 81.51 meters. Meanwhile, the greatest shoreline change due to accretion occurred at Transect 20, precisely in Kranji Hamlet, Paciran District, with a change of 92.00 meters.